Evaluating the Effectiveness of Intensive English Course in Islamic Higher Education - Ary Setya Budhi Ningrum; Toyyibah (JEELS (Journal of English Education and Linguistics Studies), 2022)
In the English Education department of the State Islamic Institute (IAIN) Kediri, there is a course so-called an Intensive English Course (IEC) program offered at the first semester. This course is designed as a preparatory program to prepare the students who come from various English proficiency backgrounds. This research is intended to evaluate the effectiveness of the IEC program. Employing a mixed-method approach, interviews, questionnaires, pre-test and post-test were administered to four Intensive English Course lecturers and 126 students. The findings of this study revealed that the program is effective as it is able to improve students’ performance, and the course material, teaching methods, and assessment conducted are appropriate. The interesting point to note is that, despite the fact that everything is well-prepared and the program has the potential to significantly improve the students' abilities, the improvement is still below par.